2017
DOI: 10.1016/j.jscs.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of a series of 1,4-disubstituted 1,2,3-triazole derivatives as possible antimicrobial agents

Abstract: Three series of novel compounds derived from 1-(2,6-difluorobenzyl)-1H-1,2,3-triazole-4-carboxylic acid bearing piperazine carboxamides, (5-(substituted phenyl)-1,3,4-oxadiazol-2-yl) and (5-(alkylthio)-1,3,4-oxadiazol-2-yl) substitutions at the 4-position were synthesized. Synthesized compounds were characterized by 1 H NMR, 13 C NMR and mass spectral analysis and evaluated for their antimicrobial activities. Interestingly, most of the compounds exhibit moderate to good activities against tested Gram-positive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…According to the reports by Jain et al 94 , 1-(4-chlorophenyl)-1-propyl piperazine and 1-(4-methylphenyl)-1-propyl piperazine exhibited excellent inhibitory activity against S. aureus and P. aeruginosa respectively. Jadhav et al 95 reported strong antibacterial and antifungal activity by different piperazine group of compounds. Thus, it can be concluded that propanoic acid decyl ester, propanoic acid,3-mercapto-dodecyl ester, 3-(phenylmethyl)-2,5-piperazinedione and N-acetyl-3-methyl-1,4-diazabicyclo[4.3.0]nonan-2,5-dione present in EA-Kz-24 might have a significant role to play in its inhibitory effect against a wide range of test microorganisms which is reported for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…According to the reports by Jain et al 94 , 1-(4-chlorophenyl)-1-propyl piperazine and 1-(4-methylphenyl)-1-propyl piperazine exhibited excellent inhibitory activity against S. aureus and P. aeruginosa respectively. Jadhav et al 95 reported strong antibacterial and antifungal activity by different piperazine group of compounds. Thus, it can be concluded that propanoic acid decyl ester, propanoic acid,3-mercapto-dodecyl ester, 3-(phenylmethyl)-2,5-piperazinedione and N-acetyl-3-methyl-1,4-diazabicyclo[4.3.0]nonan-2,5-dione present in EA-Kz-24 might have a significant role to play in its inhibitory effect against a wide range of test microorganisms which is reported for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, 1,3,4‐thiadiazole, 1,3,4‐oxadiazole, and 1,2,4‐triazole substituents are known as the most active isomers. However, chemotherapy still remains the most significant application field for heterocyclic compounds …”
Section: Introductionmentioning
confidence: 99%
“…They are known to possess a wide range of pharmacological activities like anti-microbial, 9,10 anti-inammatory, 11 anti-tubercular, 12 anti-diabetic, 13 anti-malarial, 14 antioxidant, 15 and anti-cancer activities. The basic heterocyclic rings present in various medicinal agents are mainly 1,2,3-triazoles and pyrazoles.…”
Section: Introductionmentioning
confidence: 99%